Emotions, technology, and digital games - Tettegah, Sharon Y.; Huang, Wenhao David (Emotions and technology., 2016)
"Emotions, Technology, and Digital Games explores the need for people to experience enjoyment, excitement, anxiety, anger, frustration, and many other emotions. The book provides essential information on why it is necessary to have a greater understanding of the power these emotions have on players, and how they affect players during, and after, a game. This book takes this understanding and shows how it can be used in practical ways, including the design of video games for teaching and learning, creating tools to measure social and emotional development of children, determining how empathy-related thought processes affect ethical decision-making, and examining how the fictional world of game play can influence and shape real-life experiences. Details how games affect emotions--both during and after play ; Describes how we can manage a player's affective reactions ; Applies the emotional affect to making games more immersive ; Examines game-based learning and education ; Identifies which components of online games support socio-emotional development ; Discusses the impact of game-based emotions beyond the context of games"--Provided by publisher